How sport teaches values? The specific ability of intense bodily commitment to enhance norm adherence - Tess Kate Schweizer; Maxime Mauduy; Juan M. Falomir-Pichastor; Nicolas Margas (Bern Open Publishing, 2023)
Introduction Teaching norms and values through sport and physical education (PE) is a worldwide expectation (European Parliament, 2007; International Olympic Committee, 2020), even though little is known about processes that could explain such expectation (Hatzigeorgiadis et al., 2013). Identifying them is fundamental to overcome this ideology and to improve educational programs through sport. As personal values are built according to salient social norms (Jonas et al., 2008), past research in sport and educational sciences focused on identifying salient norms and values during sport practices (e.g., Whitehead et al., 2013) and on pointing out how teachers/stakeholders can make educational norms and values salient during practice (e.g., Koh et al., 2016). We propose that the singularity of sport and PE to build values does not (only) come from the type of salient values but rather from the specific capacity of sport and PE contexts to enhance adhesion to salient norms. Indeed, sport and PE place practitioners in front of challenges that require bodily commitment and induce specific emotional context of threat and arousal of the sympathetic nervous system. Because such emotional contexts enhance adhesion to ingroup norms (Fritsche & Jugert, 2017; Hart et al., 2005; Swann et al., 2010), two studies aim to demonstrate that bodily commitment in sport and PE increases adherence to salient ingroup norms. We hypothesize a normative salience effect (H1) and a norm salience x bodily commitment interaction effect (H2) on adolescents' personal values and behavioral consequences. Method Two studies conducted in PE followed a 2 (norm salience) x 2 (bodily commitment) factorial design. One hundred and thirty-nine students (Mage = 13.97; ± 0.72; 62.1% girls, aged 13-16) took part to Study 1 and 187 (Mage = 13.59; ± 0.76; 61.5% girls, aged 12-16) to Study 2. Based on a priori power calculation (package simr, Green & Macleod, 2016), these sample size allowed us to have a sufficient statistical power of 95%. Participants first completed a preliminary questionnaire measuring personal values (Louis et al., 2009; Schwartz, 2011). Two weeks later, they participated one by one to the experimental phase. An ingroup norm was made salient, either the experimental one (pro-environmental in Study 1, healthy eating in Study 2) or the control one (anti-discrimination in Study 1 and 2), by presenting manipulated results to the preliminary questionnaire, in the form of graphic figures (Study 1) or pictures (Study 2; Gabarrot et al., 2009). They then had to do a physical exercise with weak or strong bodily commitment in climbing (Study 1) or gymnastic (Study 2). Finally, a questionnaire measured personal values (repeated measure), emotional states (arousal and threat), pro-environmental behavioral intentions (Study 1) and social desirability (Study 2) (S-CSD, Miller et al., 2014). Healthy eating self-reported behaviors were assessed one week later (Study 2). Data were analyzed using contrast with bootstrapping method as recommended by many authors (Judd et al., 2017): C1 tested the norm salience effect, C2 the bodily commitment effect in the experimental norm salience condition and C3 the bodily commitment effect in the control norm salience condition. To support our hypotheses, after controlling for initial personal values, classroom level, and social desirability effects, C1 and C2 had to be significant while C3 did not on the personal values. Then, mediating effects of our conditions on behavior measures through changes in personal values were tested. Finally, a two-studies meta-analysis was conducted on personal values and the role of arousal and threat states in producing changes in personal values was explored. Results First, bootstrap linear mixed models revealed that, in Study 1, pro-environmental personal values at T1 were positively and significantly predicted by initial pro-environmental values (Estimate = 0.72, SE = 0.05, p < .001), C1 (Estimate = 0.22, SE = 0.10, p < .05) and C2 (Estimate = 0.30, SE = 0.11, p < .01) but not by C3 (p > .05). In Study 2, the model indicated that healthy eating personal values at T1 were predicted by initial healthy eating values (Estimate = 0.64, SE = 0.03, p < .001), social desirability (Estimate = 0.64, SE = 0.09 p < .05) and C1 (Estimate = 0.34, SE = 0.09, p < .01). The influence of C2 was marginally significant (Estimate = 0.28, SE = 0.13, p = .051), while C3 (p > .05) was not significant. Second, multilevel longitudinal mediation models revealed, for Study 1, significant indirect effects of C1 (p = .03) and C2 (p = .02) on behavioral intentions through changes in pro-environmental values at T1, and for Study 2, a significant indirect effect of C1 (p = .029) on healthy eating behaviors at T2, through changes in healthy eating values at T1. Finally, the meta-analysis revealed that both C1 (d = 0.31) and C2 (d = 0.30) were positive and significant. Analyses on threat and arousal states revealed that, in Study 1, strong compared to weak bodily commitment induced greater threat states (ps < .001), although not impacting participants' changes in pro-environmental values. In Study 2, strong compared to weak bodily commitment induced greater threat than arousal states in normative salience context (Estimate = 0.30, SE = 0.14, p = .036) and only pupils' subjective threat significantly impacted changes in healthy eating personal values (p = .04). Discussion Results support our hypotheses, as changes of adolescents' personal values are explained by normative salient context (H1) and the intensity of bodily commitment in this context of norm salience (H2). Effects were obtained in two studies varying bodily commitment (climbing and gymnastic task), ingroup norm (pro-environmental and healthy eating) and salience induction (graphic figures and pictures). Exploratory analysis highlighted behavioral consequences of adolescents' changes in personal values and the specific role of threat states. Thus, these results point to a new way of explaining the singularity of sport in effectively constructing personal values of adolescents and orienting their consecutive behaviors (Agenda 2030, United Nations Educational, Scientific and Cultural Organization, 2016): First, particular attention must be paid to norms and values that are salient in sport and PE contexts and second, intense bodily commitment, especially those inducing subjective threat, are required for sport and PE to embrace their educative role. Nevertheless, our results do not suggest to only nurture threat states in sport and PE. Finally, we point to the importance of ingroup norms in the norm adherence process, but this is true whatever these norms are, and teacher/stakeholder cannot always orient the type of ingroup norm made salient during practice.   References European Parliament. (2007). The on the role of sport in education. https://www.europarl.europa.eu/doceo/document/A-6-2007-0415_EN.html Fritsche, I., & Jugert, P. (2017). The consequences of economic threat for motivated social cognition and action. Current Opinion in Psychology, 18, 31-36. https://doi.org/10.1016/j.copsyc.2017.07.027 Gabarrot, F., Falomir-Pichastor, J. M., & Mugny, G. (2009). Being similar versus being equal: Intergroup similarity moderates the influence of in-group norms on discrimination and prejudice. British Journal of Social Psychology, 48(2), 253-273. https://doi.org/10.1348/014466608X342943 Green, P., & MacLeod, C. J. (2016). SIMR: An R package for power analysis of generalized linear mixed models by simulation. Methods in Ecology and Evolution, 7(4), 493-498. https://doi.org/10.1111/2041-210X.12504 Hart, J., Shaver, P. R., & Goldenberg, J. L. (2005). Attachment, self-esteem, worldviews, and terror management: Evidence for a tripartite security system. Journal of Personality and Social Psychology, 88(6), 999-1013. https://doi.org/10.1037/0022-3514.88.6.999 Hatzigeorgiadis, A., Morela, E., Elbe, A.-M., Kouli, O., & Sanchez, X. (2013). The integrative role of sport in multicultural societies. European Psychologist, 18(3), 191-202. https://doi.org/10.1027/1016-9040/a000155 International Olympic Committee. (2020). Olympic Charter. International Olympic Committee. https://stillmed.olympic.org/media/Document%20Library/OlympicOrg/General/EN-Olympic-Charter.pdf Jonas, E., Kayser, D., Martens, A., Fritsche, I., Sullivan, D., & Greenberg, J. (2008).